An improved foraging heuristic considering reduced fog latency. (22nd January 2020) - Wang, Qing; Luo, Hai‐Wei; Xiong, Jian
Summary: Most often, in centralized distributed computing, users are getting impatient by experiencing the delays in loading the content of the web applications over the internet; it is usually caused by the poor latency management and is becoming a catastrophic situation in availing the services and applications of the centralized‐cloud computing; cloud being a distributed platform, its customers are facing the latencies issues at the various tiers of the cloud. Workloads distributions are occurring concurrently on various virtual cloud platforms. Latency‐oriented applications and services usually in cloud platform are running over various virtual machines and possess the high complexities while interacting and face the difficulties in the consolidations of the various applications containing heterogenetic workloads. In this paper, we study the fog computing and consider that it will be a feasible platform to get rid of the cloud high‐latency issues and to reduce the delay time and workflow across the network. The main purpose is to enhance the latency across the various nodes in a network. The factors like interference, availability, and interaction among various participating nodes with nearer VMware are of importance for reducing the latencies. Reduced latencies will enhance the quality of service parameters, resources, and services availability. Latency can be an important factor for the resource optimization issues in cloud computing. The comparisons with existing technologies greatly show that latency in fog is quite efficient than in the cloud paradigm. Abstract : The main purpose is to enhance the latency across the various nodes in a network. The factors like interference, availability, interaction among various participating nodes with nearer VMware are of importance for reducing thelatencies. Reduced latencies will enhance the quality of service parameters, resources and services availability.